Community acceptance studies in the field of vertical farming—A critical and systematic analysis to advance the conceptualisation of community acceptance in Kuala Lumpur. Issue 3 (2nd September 2021) - Kalantari, Fatemeh; Akhyani, Narges
ABSTRACT: Vertical farming (VF) is a new idea for supplying food inside the cities. Therefore, there is a lack of academic research concerning community acceptance (CA) of VF. This study aims to identify the CA factors of VF in Kuala Lumpur (KL). The results are based on interviews with experts as well as a questionnaire survey, that says eight factors, Perceived Benefit, Perceived Risk, Location, Demographic characteristics, Value and Belief, Trust, Fairness, and Knowledge are affecting the CA of VF in KL. Also, the results revealed that the analysis of the related literature was different from the significant factors. Then the underlying components of these factors were identified and a new framework was developed. The findings of this study could positively contribute to knowledge generation, stakeholder network establishment, new project implementation, and improvement of the general perception of VF.